Fine-needle aspiration of thyroid nodule: correlating malignant histology outcomes with cytology results in Hospital Sultanah Nur Zahirah (2011-2015) - Yusoff, Yusri Rahimi Jusoh @ Mohd (2018)
Introduction: Thyroid nodule is increasingly important especially in a case of suspicious for malignancy. FNAC is a gold standard for assessment of thyroid nodule. It also imperative as a tool to ‘rule in’ malignancy as proper surgical excision can be planned and to ‘rule out’ malignancy to prevent unnecessary surgery. US can act as adjunct to further evaluate the thyroid nodule especially when nodule is small (<1cm) and not palpable. Objective: The main objective is to study the agreement between cytopathology and histopathology in thyroidectomy patients and to identify the associated risks of malignancy in patients with thyroidectomy. Methods: Between January 2011 and December 2015, patients who underwent thyroidectomy with preoperative FNAC in Hospital Sultanah Nur Zahirah, Kuala Terengganu were reviewed. The demographic data were collected and documented. Analysis and comparison of final histopathology were conducted and the specificity and sensitivity study of thyroid FNAC were calculated and recorded. The discussion for associated risk for thyroid malignancy including age, gender, race, thyroid status, symptomatic nodule and pre-operative ultrasound finding. Results: 301 patients (274 female 27 male) had thyroid surgery. The pre-operative cytological diagnosis was made according to following categories: Benign, AUS, Follicular lesion, Malignant and Inadequate sampling. There are 141 cases in benign cytology category, 34 cases from follicular category, 19 patients from malignant category and 62 patients from inadequate sampling group. The agreement between cytopathology and histopathology was K = 0.44 with 95% CI = (0.35, 0.53). Kappa value shows that cytopathology and histopathology has moderate agreement in determining malignant and non-malignant in this study. The overall results showed a sensitivity of 63%, specificity of 81%, and positive predictive value of 61%, negative predictive value of 82% and diagnostic accuracy of 75%. Conclusion: We conclude that FNAC is a valuable and minimally invasive procedure for pre-operative assessment of patients with thyroid nodules. FNAC has high sensitivity in picking up thyroid malignancy in thyroid and has high diagnostic accuracy in the evaluation of thyroid nodules.